Analysis of The Influence of Exchange, Inflation, Gross Domestic Product, Interest Rate, and The Amount of Money Circulation On The LQ45 Index In The Indonesia Stock Exchange Between 2016-2020 - Abdul Rahman Nurmansyah; Hakiman Thamrin (Ridwan Institute, 2022)
The objective of this research was to analyze the short and the long-run relationship between five macroeconomics variables such as exchange rate, inflation, Gross Domestic Product (GDP), SBI rate, and money supply to examine their influence on the LQ45 stock price index. The data sample used in this study is monthly time series data from January 2016 to December 2020. This study used Vector Error Correction Model to analyze the problem. The result shows that in the short run (1 month ago), exchange rate, inflation, Gross Domestic Product (GDP), SBI rate, and money supply do not influence the LQ45 stock price index. In the long run, the exchange rate has positive inflation, SBI rate, and money supply negatively influence the LQ45 stock price index. Therefore, Gross Domestic Product (GDP) does not influence the LQ45 stock price index. The results of the Impulse Response Function and Variance Decomposition, SBI rate, is a variable that provides the most significant contribution to the LQ45 stock price index